Strategic Decision-Making for Greenomina Decarbonization Efforts at PT Pertamina (Persero) - Fitriastuti, Fransisca; Sunitiyoso, Yos (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2026)
This study explores the strategic decision-making process in implementing Greenomina, a digital transformation platform developed by PT Pertamina (Persero), a reputable state-owned energy company in Indonesia, to support decarbonization initiatives through carbon emission tracking and management. The analysis draws upon two frameworks: the Business Model Canvas (BMC) and the Digital Transformation Canvas (DTC). Greenomina primarily targets Scope 3 emissions, or indirect emissions from business travel and activities, by enabling employees to measure, document, and offset their carbon footprints. This study employed a qualitative approach, combining in-depth interviews and document analysis. The findings highlight key components of a successful digital business model, challenges in adopting digital solutions, and the role of digitalization in enhancing energy efficiency. Greenomina significantly improves transparency, employee engagement (specifically within the state-owned enterprise (SOE) ecosystem, and operational flexibility, aligning with national sustainability goals. Policy recommendations include strengthening digital infrastructure, fostering cross-sector collaboration, and incentivizing employee participation to expand the impacts of the platform across the energy sector in Indonesia.